Mapping of quantitative trait loci for blood pressure and cardiac mass in the rat by genome scanning of recombinant inbred strains. - Pravenec, M; Gauguier, D; Schott, J; Buard, J; Kren, V; Bila, V; Szpirer, C; Szpirer, J; Wang, J; Huang, H (1995)
In the HXB and BXH recombinant inbred strains derived from the spontaneously hypertensive rat and the normotensive Brown Norway rat, we determined the strain distribution patterns of 500 genetic markers to scan the rodent genome for quantitative trait loci regulating cardiac mass and blood pressure. The markers spanned approximately 1,139 cM of the genome and were tested for correlations with left ventricular mass adjusted for body weight, and with systolic, diastolic, and mean arterial pressures. The marker for the dopamine 1A receptor (Drd1a) on chromosome 17 showed the strongest correlation with left ventricular heart weight (P = .00038, r = -0.59) and the relationship to heart weight was independent of blood pressure. The markers showing the strongest correlations with systolic, diastolic, and mean arterial pressure were D19Mit7 on chromosome 19 (P = .0012, r = .55), D2N35 on chromosome 2 (P = .0008, r = .56), and Il6 on chromosome 4 (P = .0018, r = .53), respectively. These studies demonstrate that the HXB and BXH strains can be effectively used for genome scanning studies of complex traits and have revealed several chromosome regions that may be involved in the genetic control of blood pressure and cardiac mass in the rat.